Analytical study to raise the sensitivity of sodium analysis using Flame Photometer method and its application on pharmaceutical preparation samples available in local market (Latakia University Journal -Medical Sciences Series, 2023)
The type of linear relationship was studied between the concentrations of a standard solutions Ci of the element sodium and the intensity of the release for each of them in order to ensure that there is a correlation between them and thus evaluate the type of linear relationship. The effect of the counting of positive and negative ions and the type of medium on the signal intensity of this element was studied in order to find the optimal conditions for its determination by flame spectroscopy and thus determining it in realistic samples with high accuracy and high analysis sensitivity.The results that were reached showed that there is an excellent linear relationship between the intensity of the release and the concentrations of this element, and this was confirmed by the value of the correlation coefficient R2 = 0.99 for the resulting standard curve.It was observed that there was a positive effect of the chlorine ion Cl- on the intensity of emission of sodium, reaching a maximum of 15.8% at a concentration of 500 µg/ml, and the sulfate ion SO42- recorded a negative effect on the intensity of emission of sodium, where the percentage of decrease in the intensity of emission of sodium was 23% at a concentration of 500 µg/ml . The increase in the intensity of the release was 23% in a medium of hydrochloric acid with a concentration ranging between 0.05-0.5 N, and the effect of both nitric acid and acetic acid was weak.The results also indicated a significant increase in the intensity of emission, reaching 37.1% at a concentration of 1500 µg/ml of calcium ion, When applying the optimal conditions, the sensitivity of the analysis in some pharmaceutical preparations was raised by 33% and a return or refund was obtained by 134%. The results of this study indicated that a detection limit of 0.29 µg/ml was reached, in comparison with the results of the study conducted without applying the optimal conditions.